PENGARUH MEDIA TANAM TERHADAP PERTUMBUHAN BIBIT MERBAU (Intsia bijuga) DI PERSEMAIAN JURUSAN KEHUTANAN, FAKULTAS PERTANIAN UNIVERSITAS PATTIMURA - Komala, Vilda; Siahaya, Ludia; Tetelay, Febian (MARSEGU : Jurnal Sains dan Teknologi, 2024)
Merbau (Intsia bijuga) is a particularly good kind of timber found in the Indonesian forest and is of high economic value. They grow in the primary forests of dry land and where water is not or at times flooded, upon sandy or rocky soil, on a flat or inclined field. The most developed techniques of cultivation were with crop media. The growth of pepper seedlings is good and productive if the growing media is also supportive. The purpose of this study is to know how a growing media can affect the growth of a ripe seed. The study was conducted in the forestry department, the school of agriculture at the university of pattimura in April 2024. The design used in this study is a complete random (ral), a land media factor (m) of 4 degrees of m0 = earth (control), m1 = ground + chaff + chicken coop (1:1:2), m2 = ground The impact of planting is very real to high, and the number of ripe seed leaves is palpable, but not real to the diameter and percentage of living seeds. A mixture of soil, charcoal chaff, and manure for 1:1:2 May be the best medium to help support the growth of the smelling seed.